Discovery of WASP-174b: Doppler tomography of a near-grazing transit. Issue 4 (13th August 2018) - Temple, L Y; Hellier, C; Almleaky, Y; Anderson, D R; Bouchy, F; Brown, D J A; Burdanov, A; Cameron, Collier; Delrez, L; Gillon, M; Hall, R; Jehin, E; et al.
ABSTRACT: We report the discovery and tomographic detection of WASP-174b, a planet with a near-grazing transit on a 4.23-d orbit around a V = 11.9, F6V star with [Fe/H] = 0.09 ± 0.09. The planet is in a moderately misaligned orbit with a sky-projected spin–orbit angle of λ = 31° ± 1°. This is in agreement with the known tendency for orbits around hotter stars to be misaligned. Owing to the grazing transit, the planet's radius is uncertain with a possible range of 0.8–1.8 RJup . The planet's mass has an upper limit of 1.3 MJup . WASP-174 is the faintest hot-Jupiter system so far confirmed by tomographic means.